Pelatihan Menjadi Kreatif Tanpa Batas Dalam Pembuatan Konten Dengan AI Sebagai Pendukung Kegiatan Organisasi Bagi Pemuda JPRMI Jakarta - Sita Anggraeni; Syaifur Rahmatullah; Achmad Rifai (CV. Multi Kreasi Media, 2025)
The Young Generation or known as Gen-Z is known to have been exposed to technology from an early age, and is closer to the rapid development of technology, it triggers the younger generation to easily understand technology and can easily adapt it in everyday life. Gen-Z grew up with AI technologies such as virtual assistants (Siri, Alexa), recommendation systems (Netflix, Spotify), and AI-based learning applications, AI enables personalization of user experience across multiple platforms, something that is highly valued by Gen-Z. The urgency of the latest AI technology that can generate unique content (ranging from ideas to content in the form of text, images, audio, video, synthetic data, program code, etc.), makes it easier to create websites with digital and automation stages. Some Gen-AI products that are widely used by the younger generation include ChatGPT, DALL-E, Midjourney, etc. which are now often useful in various daily needs. Jaringan Pemuda & Remaja Masjid Indonesia (JPRMI) has many positive activities in the organization but does not have the skills in making content using AI (Artificial Intelligence) and does not have the skills in making creative content concepts that are able to target the audience appropriately. The end of this training has the aim of understanding the knowledge and skills in terms of content creation using AI (Artificial Intelligence) and understanding the steps in creating creative content concepts that are able to target audiences precisely, accurately, effectively and efficiently for the management of the Indonesian Mosque Youth & Youth Network (JPRMI) in organizational activities.